On the convergence of operator splitting for the Rosenau-Burgers equation - Zurnaci, Fatma; Seydaoglu, Muaz (WILEY, 2019)
We present convergence analysis of operator splitting methods applied to the nonlinear Rosenau-Burgers equation. The equation is first splitted into an unbounded linear part and a bounded nonlinear part and then operator splitting methods of Lie-Trotter and Strang type are applied to the equation. The local error bounds are obtained by using an approach based on the differential theory of operators in Banach space and error terms of one and two-dimensional numerical quadratures via Lie commutator bounds. The global error estimates are obtained via a Lady Windermere's fan argument. Lastly, a numerical example is studied to confirm the expected convergence order.
Keywords: convergence analysis; operator splitting; Rosenau-Burgers equation